Analysis of the Market Risk Sources in the Small and Medium-Sized Enterprises of Transport - Maria Hudakova; Jan Dvorsky (Communications - Scientific letters of the University of Zilina, 2019)
The aim of this paper was to define the important market risk sources in the transport small and medium-sized enterprises segment. A part of this aim is to find out how entrepreneurs evaluate these sources, and quantify the differences in their evaluation based on the entrepreneur’s characteristics, such as nationality, age, gender and others. The questionnaire was completed by 122 enterprises from Slovakia, Poland, the Czech Republic and Serbia. Statistical tools such as pivot tables, percentages and goodness-of-fit tests were applied to verify the formulated hypotheses. The most important source of market risk is a strong competition in the line of business. The obtained education of entrepreneurs is statistically significant characteristics for the evaluation of the market risk sources in selected transport enterprises. The findings are important for state institutions and their support systems in the transport SMEs segment.